2016
DOI: 10.1007/978-3-319-22533-3_19
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a New Minimally Invasive Intracranial Pressure Monitoring Method by Direct Comparison with an Invasive Technique

Abstract: In this chapter we present in vivo experiments with a new minimally invasive method of monitoring intracranial pressure (ICP). Strain gauge deformation sensors are externally glued onto the exposed skull. The signal from these sensors is amplified, filtered, and sent to a computer with appropriate software for analysis and data storage. Saline infusions into the spinal channel of rats were performed to produce ICP changes, and minimally invasive ICP and direct Codman intraparenchymal ICP were simultaneously ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 6 publications
1
19
0
4
Order By: Relevance
“…Twelve (41%) patients had abnormal mCBFV; low mCBFV (< 40 cm/s) were observed in two patients, and elevated mCBFV (> 70 cm/s) were observed in ten patients. ; p = 0.58), eICP (13 [9][10][11][12][13][14][15][16][17][18][19][20][21] vs. 14 [10][11][12][13][14][15][16][17][18][19][20] mmHg; p = 0.96) and eCPP (68 [60-75] vs. 75 [60-85] mmHg; p = 0.09) were similar between the two assessments. Table 3 shows the concordance between abnormal values for the different parameters measured on rst assessment; most of patients abnormal eICP also had abnormal PI aor P2/P1 values.…”
Section: Discussionmentioning
confidence: 87%
“…Twelve (41%) patients had abnormal mCBFV; low mCBFV (< 40 cm/s) were observed in two patients, and elevated mCBFV (> 70 cm/s) were observed in ten patients. ; p = 0.58), eICP (13 [9][10][11][12][13][14][15][16][17][18][19][20][21] vs. 14 [10][11][12][13][14][15][16][17][18][19][20] mmHg; p = 0.96) and eCPP (68 [60-75] vs. 75 [60-85] mmHg; p = 0.09) were similar between the two assessments. Table 3 shows the concordance between abnormal values for the different parameters measured on rst assessment; most of patients abnormal eICP also had abnormal PI aor P2/P1 values.…”
Section: Discussionmentioning
confidence: 87%
“…Yue et al[139] showed a positive correlation between increasing ICP and skull deformation. However, the concept of skull elasticity as a non-invasive modality of ICP monitoring is still in its infantile stages[139,140].…”
Section: Skull Elasticitymentioning
confidence: 99%
“…The waves and pulses of intracranial pressure reach the skull causing expansions and retractions in its volume. The Braincare sensor is able to detect these changes and convert them into numerical values that are interpreted in real time and shown as graphs for the interpretation of health professionals ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%